1975
DOI: 10.1073/pnas.72.8.3201
|View full text |Cite
|
Sign up to set email alerts
|

Binding of autologous erythrocytes to immature T-cells.

Abstract: A small percentage of normal mouse thymus and spleen lymphocytes form rosettes with autologous erythrocytes. The number of these autologous rosettes increases 15-to 20-fold after adult thymectomy and to a lesser degee with aging. Autologous rosette level is also abnormally high in nude (congenitally athymic) mice. The high level of autolo gous rosette-forming celmsfound after adult thymectomy is normalized by injecting ng amounts of purified circulating thymic factor. Autologous rosette-forming cells adhere to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
19
1
2

Year Published

1977
1977
1991
1991

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 15 publications
3
19
1
2
Order By: Relevance
“…Koskimies and M~ikel~i (18) reported that T-cell-deficient mice made stronger anti-hapten responses to conjugates of syngeneic erythrocytes than to conjugates of allogeneic or xenogeneic erythrocytes. These findings, together with others demonstrating that an appreciable fraction of murine lymphocytes form rosettes with autologous, but not with isologous, erythrocytes (19)(20), support the existence on at least some immunocytes of a receptor for a self-marker which is expressed on erythrocytes.Because this form of self-recognition is likely to be of significance for a complete understanding of the mechanisms of lymphocyte activation, it was of interest to further investigate the phenomenon of autologous rosette formation. The present study confirms the phenomenon, establishes that the receptor in question is expressed on both T and B lymphocytes, and that it is not immunoglobulin in nature.…”
mentioning
confidence: 65%
“…Koskimies and M~ikel~i (18) reported that T-cell-deficient mice made stronger anti-hapten responses to conjugates of syngeneic erythrocytes than to conjugates of allogeneic or xenogeneic erythrocytes. These findings, together with others demonstrating that an appreciable fraction of murine lymphocytes form rosettes with autologous, but not with isologous, erythrocytes (19)(20), support the existence on at least some immunocytes of a receptor for a self-marker which is expressed on erythrocytes.Because this form of self-recognition is likely to be of significance for a complete understanding of the mechanisms of lymphocyte activation, it was of interest to further investigate the phenomenon of autologous rosette formation. The present study confirms the phenomenon, establishes that the receptor in question is expressed on both T and B lymphocytes, and that it is not immunoglobulin in nature.…”
mentioning
confidence: 65%
“…It is also of considerable interest that the phenomenon of autorosette-forming thymocytes can also be observed in the mouse (26,27). In this species, however, the ability to form rosettes requires histocompatibility in the L region between the T lymphocyte and the mouse erythrocytes (28)(29)(30).…”
mentioning
confidence: 99%
“…For this reason, the , specificity of R 0116-5 for STF was tested. Binding ratio of R 0116-5 to STF (4-9) was the same as that to STF, while binding to STF (6-9) and STF (8)(9) were not observed at all. Furthermore, R 0116-5 was unable to bind to 125I-[Tyr10]-STF.…”
Section: Discussionmentioning
confidence: 69%
“…To characterize the specificity of the anti-STF anti-serum, the capacities of its binding to STF fragments, STF (4-9), STF (6-9), and STF (8)(9) which are composed of C-terminal 6, 4, or 2 amino acids, were measured. Also, the c:rossreactivities of the antiserum with various gastrointestinal peptides, gastrin 17, gastrin 34 (1-15), cholecystokinin (non-sulfate), porcine gastrin releasing peptide, substance P, glucagon, neurotensin or vasoactive intestinal polypeptide, were examined.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation